Current knowledge on regulation and impairment of motility after intestinal transplantation. Issue 3 (June 2015) - von Websky, Martin W.; Kalff, Joerg C.; Schäfer, Nico
Abstract : Purpose of review: Understanding the key mechanisms impacting on intestinal graft motility is paramount for successful intestinal transplantation. In this review, we will discuss causes of graft hypomotility and hypermotility, rooted in changes of the intrinsic nervous system, local inflammatory processes, adaptive immune responses, and more. Recent findings: Recently, it has been shown that the gut microbiome closely interacts with the structural integrity and rejection processes in the small intestine. After the ischemia/reperfusion injury is overcome, the absence of rejection is important to maintain graft motor function. The interstitial cells of Cajal, with their pacemaker function, play an important role by regulating propulsive intestinal motility in the initial absence of extrinsic signaling. Local inflammatory and immunological changes in the tunica muscularis of transplanted intestines also result in dysmotility, both after ischemia/reperfusion and during rejection. Summary: Motility of the transplanted intestine is crucial for transplant outcome and depends on multiple factors. Extrinsic denervation and changes in the intrinsic intestinal nervous system, local inflammation in the tunica muscularis, acute and chronic rejection, changes in the microbiome with Toll-like receptor activation, stasis of intestinal contents with bacterial translocation, all multifactorially result in impaired graft motility. These factors must be individually acknowledged and addressed to obtain adequate graft function.